Physical Characteristics of Peat Soil in Oil Palm Plantation, Simpang Kanan Village, Simpang Kanan Subdistrict, Rokan Hilir - Syamsol Bahri; Fitra Syawal Harahap; Badrul Ainy Dalimunthe; Ika Putri Ayu Septyani; Elfi Indrawanis (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Farmers in the village of Simpang Right use marginal land, namely peat soil, to develop oil palm farming. So far, the analysis of the physical properties of peatlands in Simpang Right has never been carried out. The application of fertilizers and oil palm plant care is only based on knowledge from social media and from the knowledge of parents first, so it is important to analyze the physical properties of the soil from peatlands that have been used for oil palm cultivation. This research was conducted from September 2021 to January 2022 on oil palm agricultural land cultivated by the community in Simpang Right Village, Simpang Right District, Rokan Downstream District, Riau Province. The method used is a free grid survey method at the semi-detail survey level. The implementation of taking soil samples from 3 sample points with a distance of 100 meters in the field using a random method spread over predetermined points. The results of the research on the physical properties of peatlands show that the peat soil used for oil palm plantations in the Simpang right village has Bulk Densty.0.15gr, Total Pore Space 44.68%, Field Capacity 254.25%, Withering Point 128,88%. Overall, the physical properties of the soil in oil palm plantations in Simpang Right Village, Simpang Right District, Rokan Downstream District, Riau Province are in good condition. To increase fertility for oil palm cultivation, it can be done by providing manure and chemical fertilizers with the required dose so that it can provide growth to oil palm plants.